2019
DOI: 10.1007/s13201-019-1118-2
|View full text |Cite
|
Sign up to set email alerts
|

The significance of morphometric analysis to understand the hydrological and morphological characteristics in two different morpho-climatic settings

Abstract: Drainage morphometric parameters are important indicator to understand the hydrological and morphological characteristics of any region. Present study aims to understand the hydrological and morphological characteristics in two different morphoclimatic settings from drainage basin morphometric parameters. Remote sensing and GIS have been used as efficient tools in delineating and understanding of any drainage basin morphometry. The Kosi River basin of northern India for the mountain-plain tropical environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(68 citation statements)
references
References 32 publications
(76 reference statements)
3
55
0
4
Order By: Relevance
“…It was believed that the variation observed in the respective parameters was governed by the physiographic difference and structural condition of the watershed (Nikhil Raj and Azeez 2012; Praveen et al 2018; Biswas 2016). The consistent decrease in N u against u revealed the presence of erosional landform throughout the watershed (Avijit 2019).…”
Section: Stream Number (N U )mentioning
confidence: 83%
See 4 more Smart Citations
“…It was believed that the variation observed in the respective parameters was governed by the physiographic difference and structural condition of the watershed (Nikhil Raj and Azeez 2012; Praveen et al 2018; Biswas 2016). The consistent decrease in N u against u revealed the presence of erosional landform throughout the watershed (Avijit 2019).…”
Section: Stream Number (N U )mentioning
confidence: 83%
“…The R e values of Tikur Wuha SW were varied from 0.31 to 0.59. The result indicated that SW9 and SW10 are more elongate than others implying low peak discharge, whereas SW2, SW3 and SW11 were relatively circular in nature (Avijit 2019).…”
Section: Elongation Ratio (R E )mentioning
confidence: 87%
See 3 more Smart Citations